Psychotherapy, psychoanalysis and urban poverty in Argentina. Issue 3 (1st September 2016) - Epele, Maria Esther
ABSTRACT: Based on ethnographic research carried out in the Buenos Aires Metropolitan Area, this paper examines the views of social actors on the psychoanalytically-oriented psychotherapy focused on marginalized populations. From Foucault's perspective on the forms of truth-telling, the aim of this paper is to analyze, as a preliminary research report, treatments according to the native ways of speaking and listening, which dominate the description of therapeutic experiences of patients who come to the treatment without any professional intermediation. The neoliberal transformations of the past decades in Argentina changed both the landscape of the public health system and the daily lives of marginalized people. Considering such changes, this paper examines the ways in which verbal actions (speaking and listening) take place in psychotherapy and mark the course not only of treatments but also the temporal rhythms of their development, and their various levels of efficacy. Finally, the discussion focuses on how ways of speaking and listening in treatments are modeled not only by institutional dynamics but also by the characteristics these verbal activities take in everyday life under the logics of power that prevail over them.